PENERAPAN METODE FUZZY ANALYTIC NETWORK PROCESS DALAM MENENTUKAN LOKASI KANTOR CABANG BANK BARU DI KABUPATEN NGANJUK - Sintia Wahyu Ningrum; Raden Sulaiman (MATHunesa: Jurnal Ilmiah Matematika, 2023)
Determining the location of bank branch offices is a policy that must be taken to respond to challenges and changes in the long term, so an in-depth analysis is needed to choose the right location. Ranking is done based on the weight of the sub-criteria that have been processed using the Fuzzy Analytic Network Process (FANP) method. Weight calculations are also based on dependencies, both inner and outer dependencies. The existence of interrelationships between sub-criteria with one another makes the Fuzzy Analytic Network Process (FANP) method more complex than other decision-making techniques. Based on the calculation of the Fuzzy Analytic Network Process (FANP) method, the weight of each sub-criteria is obtained, namely the population of 8.62%, population density of 12.95%, land area of 4.65%, security facilities of 24.65%, availability of public utilities of 2.62%, location distance to settlements of 12.53%, the closest distance between fellow branches of 33.09%, and the number of competitors of 0.90%. Keywords: Bank location determination, Fuzzy Analytic Network Process (FANP), fuzzy, analytic network process, inner dependence.